LOYALITAS KARYAWAN DITINJAU DARI PENGEMBANGAN KARIR, KOMPENSASI DAN STRES KERJA - Siti Mahmudah; Ariyani Indriastuti; Theresia Susetyarsi (Sekolah Tinggi Ilmu Ekonomi Semarang, 2020)
Abstract. This research objective to analyze the factors that affect employee loyalty. The results showed that career development has a significant positive effect on employee loyalty, compensation has a significant positive effect on employee loyalty, job stress has a significant negative effect on employee loyalty.